Solar energy sciences and engineering applications - Enteria, Napoleon (CRC Press, 2013)
"Solar energy is available all over the world in different intensities. Theoretically, the solar energy available on the surface of the earth is enough to support the energy requirements of the complete planet. However, in reality, progress and development of solar science and technology depends to a large extend on human desires and needs. This is due to the various barriers to overcome and to deal with the economics of practical utilization of solar energy. The book will introduce the rapid development and progress in the field of solar energy applications for science and technology: the advancement in the field of biological & chemical processes; electricity production; mechanical & building operations enhanced by solar energy. The book covers biofuel, enzymes and other biological processes related to solar energy; chemical processes for the production of hydrogen from water and natural gas and other endothermic processes using solar energy; the development of the thermoelectric production through solar energy; the development of solar ponds for electric energy production; the mechanical operation with solar energy; the building operation with solar energy optimization. The book is an invaluable resource for scientists who need the scientific and technological knowledge of the wide coverage of solar energy sciences and engineering applications. This will further encourage researchers, scientists, engineers, and students to stimulate the use of solar energy as an alternative energy source"